ANALISIS PERTUMBUHAN TEKNOLOGI, PRODUK DOMESTIK BRUTO, DAN EKSPOR SEKTOR INDUSTRI KREATIF INDONESIA - Nandha Rizki Awalia; Sri Mulatsih; Dominicus Savio Priyarsono (IPB University, 2013)
Creative industries are seen to be important for the economic well-being, proponents suggesting that human creativity is the ultimate economic resource. This research seeks to explore the technology progress measured by total factor productivity (TFP) growth of creative industry in Indonesia, analyze how external factors influence GDP of creative industry (education, TFP growth, the number of companies, the number of labors, and government policy), and analyze the causality between GDP and export of creative industry using Granger Causality Test. This research uses panel data, representing pooled of time series data (year 2006-2013) and cross section data (14 subsectors of creative industry). The results shows that (1) TFP growth of 4 creative industry subsectors are negative: architecture, interactive games, computer programs, and research and development; (2) factors influencing the GDP of creative industry positively: education, TFP growth, the number of labors, and government policy; (3) there is two-way-causality between GDP and export of creative industry. Keywords: creative industry, TFP, panel data, Granger causality.